Information and communication is reputation warning system for computer lab - LIU XIAOCUI; WANG CHENCHEN; LI JIE; LI JIAN; FU ZHENG; JIANG PING; ZHOU XIAOFEN; YOU MIN; YANG QICHAO (2015)
The utility model relates to an information and communication is reputation warning system for computer lab, report an emergency and ask for help or increased vigilance module, message routing module, system management module including data acquisition module, data processing module, data storage module, reputation, data acquisition module connects data processing module, data processing module and data storage module both -way communication, and data processing module and system management module both -way communication, data processing module connect the reputation and report an emergency and ask for help or increased vigilance module and message routing module. The utility model discloses a to the all -round control of information and communication computer lab, data acquisition carries out, in case break down, in time sends the alarm and reminds to keep monitoring record, in time investigate the potential safety hazard.